The Revised Arabic Scale of Obsession-Compulsion (ASOC): Validation with Iranian psychiatric outpatients. Issue 3 (20th April 2020) - Dadfar, Mahboubeh; Abdel-Khalek, Ahmed M.; Lester, David
ABSTRACT: The aims of the present study were (a) to develop a Farsi version of the Revised Arabic Scale of Obsession-Compulsion (ASOC), (b) to investigate its psychometric properties, (c) to explore its correlations with another scale of obsession-compulsion, as well as scales of depression, somatic symptoms, and religiosity, (d) to explore its factorial structure, and (e) to estimate sex-related differences. A sample of 111 Iranian psychiatric outpatients was recruited. They responded to the Farsi versions of the ASOC, the Maudsley Obsessional-Compulsive Inventory (MOCI), Patient Health Questionnaire-2 (PHQ-2), Somatic Symptoms Scale (SSS), and Self-Rating Scale for Religiosity (SRR). Cronbach' α was .89 for the ASOC, and five salient components were extracted. All the correlations between the ASOC scores were statistically significant and positive with the other scales (except for the SRR scores). Patients who had more obsessive-compulsive symptoms had more depression and somatic symptoms. The sex-related difference in the ASOC was not significant. This study provides evidence for the usefulness of the ASOC for assessing OC symptoms in Iranian psychiatric outpatients and extends existing research about the measure's factor structure.